Distribution of responsibility for social security and labour market policy. Country report: Germany - Ebbinghaus, Bernhard; Eichhorst, Werner (Amsterdam, 2007)
"High levels of unemployment, or high levels of social expenditures as well as the growing demand for a flexible labour force have given new impetus to the world-wide discussion on what model to use for an efficiently operating labour market and in particular on the role of institutions. Although there seems to be a growing consensus on the restricted governmental role in recent decades, this has not been translated into a unanimous appraisal of the role of intermediary organisations, such as trade unions. There is no clear view on an appropriate distribution of responsibility between government, social partners and the market. The research project ‘distribution of responsibility for social security’ aims to create a scientific basis for a clear and consistent view on the role and distribution of responsibilities between the different labour market institutions. As part of this research project, this paper provides an elaborate country study of Germany. In short, it is shown that for both employment protection and unemployment benefits the basic features are defined by law. In that sense, government and parliament are crucial for shaping the system, following more a political logic of office-seeking and vote maximisation. The role of social partners is largely limited to collective bargaining. There are collective labour agreements on additional employment protection through sectoral or enterprise-level agreements. Private actors have become more prominent as contracting-out of active labour market policy services has grown over the last decade, most significantly in the area of job placement and training. As for the labour market performance, the German labour market is highly segmented with persistent long-term unemployment and low labour market integration of more vulnerable groups. Participation rates are modest, mainly due to low female participation and early retirement."